Imagery As a Core Process in the Creativity of Successful and Awarded Artists and Scientists and Its Neurobiological Correlates - Chavez, Rosa Aurora (Frontiers in Psychology, 2016)
This perspective paper presents an integration of neuroimaging and phenomenological data obtained in a sample that included highly creative, internationally awarded scientists and/or artists. The cerebral blood flow (CBF) was evaluated during the performance of standardized creativity tasks from the Torrance Tests of Creative Thinking (TTCT) Verbal Form. The phenomenological data comprised both, their experiences and processes related to their creative careers and their experiences during the performance of the creative thinking tasks during the acquisition of the brain imaging data. Highly creative individuals presented a significantly higher activation of areas involved in motor imagery and described that their creative process is frequently triggered by the spontaneous and often surprising emergence of what is being named here as primordial imagery: a sudden, multimodal, multiintegrative, highly condensed representation that is germinative, unleashing insight and multiple associations and possibilities for meaning. As evidenced in creativity, imagery is a process through which we perceive our own minds, allowing us further symbolization and access to our thoughts, possibly facilitating neural pathways.